Exploring community-based development : a case study of the Estate and rural community development in North Malaita, Solomon Islands : a thesis presented in partial fulfillment of the requirement for the degree of Master of Master of International Development at Massey University, Palmerston North, New Zealand - Faiau, James Kwaimani (Massey University, 2013)
This thesis is concerned with the concept of community development. In particular, the role and contribution of a community-based initiative in development will be explored. Based on the case study of the Estate, which was introduced in North Malaita in the mid-2000s, this thesis seeks to explore how this initiative contributes to positive community development, which is concerned with not only economic aspects, but also social, cultural and spiritual aspects of development. This study also seeks to understand the underling premises and development values, the success stories and positive impacts of the Estate programs and projects on people‟s lives and communities, as well as the constraints and challenges facing the Estate and rural community development in North Malaita of Solomon Islands. This study of the Estate and community development in North Malaita recognises that there is a need for a comprehensive approach to development which should focus on all dimensions of development which is concerned with the goal of improving the total wellbeing of the people, and on building a strong, healthy and functional community. The Estate has shown that this all-compassing development can be based on collective involvement of local people and institutions driving their own development. This study found that partial approaches to development that only focus on service provision, discrete initiatives, information dissemination, and provision of resources to meet perceived needs have failed to bring about tangible and transformative change and positive development in rural communities in North Malaita and Solomon Islands. Thus, a different approach is being suggested, one that is context based and inclusive, with emphasis on the role of local people to organize their own communities and to utilize local resources to drive development. Far more than a concept that is about development in the rural communities, this study embraces the notion that community development is about development of the community, which includes improvement of the total wellbeing – or the „good life‟ and keeps building a strong community.
Keywords: Community development; Rural development; Solomon Islands; Malaita, Solomon Islands